Integrating MindMeister into Morphology Learning: A Case Study of Student Reflections - Ina Daril Hanna; Rini Listyowati; Beny Hamdani (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
Morphology, as a core component of linguistics, is often considered abstract and challenging for students in English Education Programs. While digital mind mapping has been widely used in general language skills, its specific application in navigating the complex structural hierarchies of morphology remains under-explored. The crucial point of this investigation lies in the urgent need to bridge the gap between theoretical linguistic rules and students' visual-spatial conceptualization. To address this issue, this study explores students’ reflections on learning morphology through MindMeister. It offers novelty by detailing how digital visualization tools can transform abstract morphological analysis into a more tangible and reflective learning experience in an Indonesian higher education context. Employing a descriptive qualitative case study, the research involved nine third-semester students enrolled in a morphology course. Data were collected through written reflections and interview-based question sheets, then analyzed using thematic analysis. Findings revealed five major themes: (1) cognitive support and conceptual understanding, (2) affective engagement and motivation, (3) learning strategies through visualization, (4) technical and usability challenges, and (5) continued reliance on teacher explanation. Students reported that MindMeister enhanced their ability to differentiate and organize morphological concepts, increased motivation, and supported reflective and self-regulated learning strategies. However, challenges such as technical limitations and the necessity of teacher scaffolding remained evident. The study contributes to technology-enhanced linguistics pedagogy by highlighting the affordances and constraints of digital visualization tools in teaching morphology. Pedagogically, it suggests that digital mind mapping should complement, rather than replace, explicit instruction. This study is among the first to investigate student reflections on the use of digital mind mapping in morphology learning, highlighting its novelty in technology-enhanced linguistics pedagogy.